2008
DOI: 10.1055/s-2008-1047621
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotika bei nekrotisierender Pankreatitis: Ergebnisse einer kontrollierten Studie

Abstract: Antibiotic prophylaxis neither prevented nor delayed bacterial infection of the necrotic pancreas. But it significantly improved the clinical course if started before the onset of infection of the pancreatic necroses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2010
2010
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(16 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…Sainio et al [11] showed a significant reduction of mortality when prophylactic antibiotics were used; however, the primary (one-side testing) and secondary (two-side testing) outcomes did not use the same Fisher exact test. No significant difference in mortality or IPN was found in Schwarz et al’s trial [12]. The need for surgery was significantly reduced in a trial evaluating the early administration of imipenem, but in this trial only 7 patients were proven microbiologically to have IPN [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sainio et al [11] showed a significant reduction of mortality when prophylactic antibiotics were used; however, the primary (one-side testing) and secondary (two-side testing) outcomes did not use the same Fisher exact test. No significant difference in mortality or IPN was found in Schwarz et al’s trial [12]. The need for surgery was significantly reduced in a trial evaluating the early administration of imipenem, but in this trial only 7 patients were proven microbiologically to have IPN [13].…”
Section: Discussionmentioning
confidence: 99%
“…Three types of antibiotics, carbapenems, fluoroquinolones, and cephalosporins, have been found to penetrate into the pancreas [8,9]. During the past decades, a number of studies have been done in order to determine whether it is necessary to administer antibiotics for ANP with conflicting results [10,11,12,13,14,15,16,17,18]. Meta-analyses have also been inconclusive [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of our own group [21], using ofloxacin and metronidazole prophylaxis significantly improved the clinical course. Mortality could not significantly be reduced due to small patient numbers.…”
Section: Discussionmentioning
confidence: 89%
“…A shift from gram-negative bacteria to gram-positive has been reported [21,40]. Patients with pancreatic necrosis infected by Candida suffer a higher mortality compared to patients without Candida infection (64% vs 19%) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Two smaller studies had failed to confi rm these results ( table 5 ) [133,134] , but two metaanalyses of the then available data indicated that prophylactic antibiotics in patients with necrotizing pancreatitis probably has a positive effect on the course of the disease [135,136] . These results led to the recommendation of prophylactic antibiotic administration for patients with acute necrotizing pancreatitis in a number of recent guidelines and consensus recommendations ( table 3 ) [137][138][139][140][141][142][143][144] .…”
Section: Prevention Of Infected Pancreatic Necrosismentioning
confidence: 99%